2014
DOI: 10.1242/dev.113639
|View full text |Cite
|
Sign up to set email alerts
|

The sinus venosus contributes to coronary vasculature through VEGFC-stimulated angiogenesis

Abstract: Identifying coronary artery progenitors and their developmental pathways could inspire novel regenerative treatments for heart disease. Multiple sources of coronary vessels have been proposed, including the sinus venosus (SV), endocardium and proepicardium, but their relative contributions to the coronary circulation and the molecular mechanisms regulating their development are poorly understood. We created an ApjCreER mouse line as a lineagetracing tool to map SV-derived vessels onto the heart and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
285
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(336 citation statements)
references
References 37 publications
(67 reference statements)
29
285
0
6
Order By: Relevance
“…Myocardial thickness and valve structure are not perturbed in knockout hearts, which is consistent with the more restricted expression pattern of VEGF-C in the outflow tract vessels and epicardium (26). In another study, we showed that VEGF-C deletion specifically affects sinus venosus-derived coronary development but not coronary vascularization from other sources on the ventral side of the heart and septum (likely from the endocardium, refs.…”
Section: Animalssupporting
confidence: 83%
See 2 more Smart Citations
“…Myocardial thickness and valve structure are not perturbed in knockout hearts, which is consistent with the more restricted expression pattern of VEGF-C in the outflow tract vessels and epicardium (26). In another study, we showed that VEGF-C deletion specifically affects sinus venosus-derived coronary development but not coronary vascularization from other sources on the ventral side of the heart and septum (likely from the endocardium, refs.…”
Section: Animalssupporting
confidence: 83%
“…Depletion of VEGF-C had a dramatic effect. Although heart morphogenesis was grossly normal and other vessel beds were not affected (26), ASVs were completely missing and peritruncal coronary vessels were severely reduced in VEGF-C knockout animals ( Figure 3E). Heterozygous animals exhibited an intermediate phenotype (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the perivascular compartment of coronary vessels appears to derive from the epicardium (including resident CD45 + cells), recent lineage-tracing studies show that coronary endothelial cells have heterogeneous origins. The details are still being debated, but it is clear that distinct populations of endothelial cells arise from the sinus venosus and the endocardium, with a minor population deriving directly from the epicardium (Chen et al, 2014;Del Monte and Harvey, 2012;Katz et al, 2012;Tian et al, 2014;Wu et al, 2012). These populations deploy angioblasts with distinct kinetics and spatial signatures (Chen et al, 2014), with the endocardium also contributing to the coronary vascular tree postnatally during a process called trabecular compaction (Tian et al, 2014).…”
Section: The Origin Of Cardiac Lineages In Developmentmentioning
confidence: 99%
“…The details are still being debated, but it is clear that distinct populations of endothelial cells arise from the sinus venosus and the endocardium, with a minor population deriving directly from the epicardium (Chen et al, 2014;Del Monte and Harvey, 2012;Katz et al, 2012;Tian et al, 2014;Wu et al, 2012). These populations deploy angioblasts with distinct kinetics and spatial signatures (Chen et al, 2014), with the endocardium also contributing to the coronary vascular tree postnatally during a process called trabecular compaction (Tian et al, 2014). Cardiac lymphatics also have a dual origin from the endothelial cells of the cardinal veins, as well as yolk sac endothelial or hemogenic cells (Klotz et al, 2015).…”
Section: The Origin Of Cardiac Lineages In Developmentmentioning
confidence: 99%